The Influence of Seismic Load to Deformation of Dam - Undayani Cita Sari; Abdul Rochim; Windu Partono (International Conference on Coastal and Delta Areas, 2017)
Disaster mitigation due to seismic load (earthquake) needs to be considered. This is especially for dam structure used as a reservoir and water resource. Because of the main function, and building dimension is too large, thus if the dam collapse it will cause a significant catastrophe for the surrounding community and environment. One of the seismic damages to the dam is deformation. This paper presents the effect of seismic load on deformation of dam model simulation. This study took place on the Sermo Dam, Yogyakarta which is located close to Opak Fault –as the suspicious cause of the earthquake in Yogyakarta. Seismic loads used in this study in terms of acceleration time histories. Therefore model can be carried out using PLAXIS simulation. This selected seismic load variations are on the range 5.0-7.0 Mw and epicentrum distance is also restricted in 15-31 Km based on the nearest epicentrum distance between Sermo Dam and Opak Fault. Keywords: seismic load, deformation, dam, modeling